Extra Node-like nk-t cell lymphoma of the nasal type: a case report (Salud, Arte y Cuidado, 2025)
Objective: Describe the evolution, diagnosis and treatment as well as record of the case. A case is reported of a 54-year-old male patient with a diagnosis of extra-nodal T/NK Cell Lymphoma of the nasal type. Clinical Case: A 54-year-old male patient who presents with a current illness of 1 month of evolution characterized by an increase in volume in the vestibule of the right nasal fossa after local trauma in said area, which complies with antibiotic therapy without improvement. A tomography of the nose and paranasal sinuses was performed, an initial inconclusive biopsy was taken, an MRI was performed and a decision was made to take a sample for biopsy and immunohistochemistry in the operating room to decide on conduct. This report reported Extra Nodal T/NK Cell Lymphoma of the nasal type. Discussion: This pathology is a predominantly extranodal lymphoma, associated with the Epstein-Barr virus in contrast to this case, it has a nasal location, it is characterized by vascular damage with angiocentric and angiodestructive patterns similar to the reported case; whose treatment is based on chemotherapy and radiotherapy. Conclusion: Timely diagnosis and adequate treatment improves survival depending on the type of disease and stage at diagnosis, with a 5-year overall survival of 54%. This case contributes tools and knowledge to manage this rare pathology
Keywords: lymphoma; Epstein-Barr; lymph node.